Historical Dimension of the Formation of Multicultural Education in Canada - Bakhov, Ivan Stepanovich (Pedagogika, 2015)
The article is devoted to the formation of the multiculturalism policy in Canada. Main stages of Canadian history and their role in the emergence of multicultural ideology of the state are traced. Analyzing the successful Canadian experience in the effective regulation of internal national conflicts, are made conclusions about the reasons for such an efficient performance.